2018
DOI: 10.3934/dcdsb.2017199
|View full text |Cite
|
Sign up to set email alerts
|

Eventual smoothness and asymptotic behaviour of solutions to a chemotaxis system perturbed by a logistic growth

Abstract: In this paper we study the chemotaxis-system ut = ∆u − χ∇ • (u∇v) + g(u) x ∈ Ω, t > 0, vt = ∆v − v + u x ∈ Ω, t > 0, defined in a convex smooth and bounded domain Ω of R n , n ≥ 1, with χ > 0 and endowed with homogeneous Neumann boundary conditions. The source g behaves similarly to the logistic function and satisfies g(s) ≤ a − bs α , for s ≥ 0, with a ≥ 0, b > 0 and α > 1. Continuing the research initiated in [33], where for appropriate 1 < p < α < 2 and (u 0 , v 0) ∈ C 0 (Ω) × C 2 (Ω) the global existence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…When µ > 0, a number of dynamical properties have been detected both numerically and also analytically. For example, the exceedance of corresponding carrying capacities seems possible (see [7,11,12,19,23,31,34,39]). For example, when µ > 0 is small, the chemotactic cross diffusion was shown to enforce the occurrence of solutions which attain possibly finite but arbitrarily large values (see [31]).…”
Section: Jie Zhaomentioning
confidence: 99%
See 1 more Smart Citation
“…When µ > 0, a number of dynamical properties have been detected both numerically and also analytically. For example, the exceedance of corresponding carrying capacities seems possible (see [7,11,12,19,23,31,34,39]). For example, when µ > 0 is small, the chemotactic cross diffusion was shown to enforce the occurrence of solutions which attain possibly finite but arbitrarily large values (see [31]).…”
Section: Jie Zhaomentioning
confidence: 99%
“…In [19], the authors have proved that the population as a whole always persists in the sense that for any nonnegative global classical solution, there exists a lower bound for mass. In [23], it is showed that logistic dampening may prevent blow-up of solutions. Besides, when τ = 0, r = 2 and D(u) ≡ 1, the main results in [22] showed the prevention of blow up under the conditions n ≤ 2, µ > 0 or n ≥ 3, µ > n−2 n χ.…”
Section: Jie Zhaomentioning
confidence: 99%
“…Moreover, Cauchy problem is also considered in R 2 , with regular sensitivity and (1.17), in [31]. There are also recent works dealing with the existence of large data weak solutions to Keller-Segel type models with logistic growth, and we refer the reader to [18,36,37,38,39,41,44,46,51] and the references therein for more information in this direction. However, we notice that with the logarithmic sensitivity function and density-dependent production rate, no result concerning the qualitative behavior of large data solutions is available in the knowledge base.…”
Section: 23mentioning
confidence: 99%
“…23 Additionally, in the case (v) = > 0, but with source term g(s) ≃ k− s r , for s ≥ 0, and with some r > 1, global existence of very weak solutions, as well their boundedness properties and long time behaviour are discussed in other works. [24][25][26] Finally, in order to better define the purpose of this present investigation, let us frame model (1), in its parabolic-elliptic representation, in the existent literature. For m = = 1 and (v) = > 0, it is proved in Tello and Winkler 27 that when > (n − 2) ∕n the solutions are globally bounded, whilst for m ∈ R, = 1 and (v) = > 0 the same result is achieved in Cao and Zheng 28 under the assumption > (1 − 2∕(n(2 − m) + )) .…”
Section: Introduction and Motivationsmentioning
confidence: 99%